Zakat dan Pajak dalam Pandangan Masdar Farid Mas’udi - Nurhayati, Tri (Fakultas Syariah IAIN Purwokerto, 2009)
Masdar Farid Mas’udi is intended to maintain the Islamic social construction by discussing zakat historically. He defined zakat as a tax concept which combined the two concepts from the government and Islam. He offered some concepts on interpreting that dualism.